(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
The effectiveness of alkaline hydrogen peroxide as a suitable choice of pretreatment for the conversion of millet husk to reducing sugars using cellulase enzyme for hydrolysis and subsequent ethanol production was determined. The effects of three variables on reducing sugar production from millet husk were determined using one factor at a time (OFAT) method namely; peroxide concentration, pretreatment time and pretreatment temperature. From the results, it was observed that a significant (P<0.05) amount of reducing sugars were lost during pretreatment of millet husk. The untreated group which was only physically pretreated (milled) however yielded a significantly higher (P<0.05) reducing sugar concentration of 10.67mg/ml after enzymatic hydrolysis while the highest reducing sugar concentration of 4.82mg/ml was obtained using 0.375%v/v peroxide concentration for 60minutes at 250C. Therefore, pretreatment of biomass with alkaline hydrogen peroxide may be more suitable for feedstock with high lignin contents than millet husk.